INNOVATIVE METHODS IN ORGANIZING EDUCATIONAL ACTIVITIES AND PROBLEMS IN THEIR IMPLEMENTATION (Web of Teachers: Inderscience Research, 2023)
The article describes innovative methods and problems in their implementation in the organization of modern educational activities. There is also a focus on the importance of independent educational activities in education.